Gonorrhea Treatment Failures With Oral and Injectable Expanded Spectrum Cephalosporin Monotherapy vs Dual Therapy at 4 Canadian Sexually Transmitted Infection Clinics, 2010–2013. Issue 6 (June 2015) - Singh, Ameeta E.; Gratrix, Jennifer; Martin, Irene; Friedman, Dara S.; Hoang, Linda; Lester, Richard; Metz, Gila; Ogilvie, Gina; Read, Ron; Wong, Tom
Abstract : Background: Antimicrobial resistance has developed to all antibiotics used to treat gonorrhea (GC), and trends in GC antimicrobial resistance have prompted changes in treatment guidelines. We examined treatment failures in sexually transmitted infection clinics. Methods: Four Canadian sexually transmitted infection clinics reviewed treatment regimens, minimum inhibitory concentrations for cephalosporins and azithromycin, anatomical infection sites, and treatment outcomes for GC infections between January 2010 and September 2013, in individuals who returned for test of cure within 30 days of treatment. Treatment failure was defined as the absence of reported sexual contact during the posttreatment period and (i) positive for Neisseria gonorrhoeae on culture of specimens taken at least 72 hours after treatment or (ii) positive nucleic acid amplification test specimens taken at least 2 to 3 weeks after treatment, and matching sequence type pretreatment and posttreatment. χ 2 Test and Fisher exact test were used to assess association of categorical variables. Results: Of 389 specimens reviewed, GC treatment failures occurred in 13 specimens treated with cefixime 400-mg single dose (17.8% treatment failure rate regardless of anatomical site) and in 1 oropharyngeal specimen treated with cefixime 800-mg single dose. No treatment failures occurred using either ceftriaxone monotherapy or cefixime/ceftriaxone combined with azithromycin or doxycycline. Conclusions: In contrast to oral cefixime monotherapy, no treatment failures were identified with injectable ceftriaxone monotherapy or combination GC treatment. Our data support the use of combination treatment of GC with an extended spectrum cephalosporin (including oral cefixime) with azithromycin or doxycycline as well as ceftriaxone monotherapy. Abstract : In contrast to cefixime monotherapy, no treatment failures were identified with ceftriaxone monotherapy or combination treatment (cefixime or ceftriaxone with azithromycin or doxycycline) at 4 Canadian sexually transmitted infection clinics.